Pengujian Kompos Tithonia (Tithonia diversifolia) Pada Dua Varietas Sorgum (Sorghum bicolor (L.) Moench) Di Desa Siopat Sosor Kabupaten Samosir - Pieter, T., Yan; Irmansyah, T.; Mawarni, Lisa (Universitas Sumatera Utara, 2015)
The aim of this research was to know growth response and production of some sorghum varieties to the addition of tithonia compost. The research was held from July - November 2014, used randomized block design with three factors addition of tithonia compost (0, 10, and 20 ton/ha) and two varieties (Kawali and Numbu). Parameters measured were plant height,the number of leaves , flowering time, weight of panicle seed per sample, weight of panicle seed per plot, yield per sample, yield per plot, and 1000 grains weight. The result showed that compost doesn’t affected significantly on all of parameters. Varieties affected significantly on plant height, the number of leaves, flowering time, yield per sample, yield per plot, and 1000 grains weight. There were not any interaction between compost and variety on all parameters. The best result was found in the combination of 10 kg tithonia compost and numbu variety. Keywords: , tithonia, variety, compost, sorghum.